2004
DOI: 10.5032/jae.2004.01029
|View full text |Cite
|
Sign up to set email alerts
|

Engaging Students in the Agricultural Education Model: Factors Affecting Student Participation in the National Ffa Organization

Abstract: The purpose of this study was to determine the degree of engagement of agricultural education students in the FFA, their agricultural education courses, their high school courses, and agriculture. This descriptive study using self-administered mailed questionnaires had a 52% useable response rate from FFA members and a 63% useable response rate from nonmembers. Members of the National FFA Organization more than non-members had a higher percentage that were current or former 4-H members, a higher percentage tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 9 publications
0
22
0
Order By: Relevance
“…Basic demographics for the respondents are presented in Table 1. Results from a 1999 National FFA Organization study (Balschweid & Talbert, 2000;Talbert & Balschweid, 2004) are provided as a comparison. The 1999 study was a mailed questionnaire to 500 FFA members with a 52% response rate.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Basic demographics for the respondents are presented in Table 1. Results from a 1999 National FFA Organization study (Balschweid & Talbert, 2000;Talbert & Balschweid, 2004) are provided as a comparison. The 1999 study was a mailed questionnaire to 500 FFA members with a 52% response rate.…”
Section: Resultsmentioning
confidence: 99%
“…The questionnaire was modified from a 1999 National FFA Organization study (Balschweid & Talbert, 2000;Talbert & Balschweid, 2004) by adding questions and rewording questions that appeared confusing. Face, content, and construct validity was established with the assistance of management at the National FFA Organization.…”
Section: Methodsmentioning
confidence: 99%
“…Research among enrollment, FFA membership, and SAE participation has suggested positive relationships between FFA membership and SAE participation (Retallick & Martin, 2008;Talbert & Balschweid, 2004;Thompson & Shumacher, 1998;White & Pals, 2004). Research also suggested a positive economic impact resulting from SAE (Graham & Birkenholz, 1999;Retallick & Martin, 2005;West & Iverson, 1999), including a positive return on investment (Retallick & Martin, 2005).…”
Section: Introduction and Review Of Literaturementioning
confidence: 99%
“…This difference between what teachers and students believe clarifies the need to assess motivation directly from a youth participant perspective. To better understand youth participation, it is important to identify motivational factors from the youth's perspectives (Russell et al, 2009;Talbert & Balschweid, 2004) and determine relationships among youth motivation factors. Jones, Knobloch, and Orvis (2011) found that youth motivation had an important role in developing career-related competencies when participating in a Horticulture CDE.…”
Section: Introductionmentioning
confidence: 99%